2013
DOI: 10.1590/s1806-83242013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Performance of digital radiography with enhancement filters for the diagnosis of proximal caries

Abstract: Enhancement filters are potentially supposed to improve the diagnostic performance of digital images. Thus, the aim of this study was to compare the performance of digital radiography with and without enhancement filters for the detection of induced proximal caries lesions. The total sample consisted of 120 sound human teeth (40 premolars, 80 molars). Enamel subsurface demineralization was induced in one of the proximal surfaces of 60 teeth. Standardized radiographs of all teeth were acquired after the deminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
(36 reference statements)
2
30
0
Order By: Relevance
“…As seen in the results presented in the present manuscript, the application of different radiographic filters did not result in an improvement in the diagnosis of caries, corroborating the results found by Takeshita et al 3 Haiter-Neto et al 13 Booshehry et al 17 Belém et al 19 and…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As seen in the results presented in the present manuscript, the application of different radiographic filters did not result in an improvement in the diagnosis of caries, corroborating the results found by Takeshita et al 3 Haiter-Neto et al 13 Booshehry et al 17 Belém et al 19 and…”
Section: Discussionsupporting
confidence: 92%
“…An advantage of the ROC analysis is that it reflects the diagnostic performance of the method based on sensitivity and specificity. 5,11,19 These groups were evaluated by three examiners, specialists in Dental Radiology and Imaging Exams, suing the scale of evaluation, whose data were submitted to the Kappa interexaminer (KW = 0.799) and intraexaminer tests: examiner A (KW = 0.817), examiner B (KW = 0.931) and examiner C (KW = 0.841). In order to interpret these results Landis and Koch, 20 presented a scale that goes from < 0 up to 1.00, with the interval between 1.00 and 0.81 representing almost perfect agreement and between…”
Section: Methodsmentioning
confidence: 99%
“…Negative, sharpen and both were applied to enhance images. The authors reported that the sharpen filter demonstrated the highest performance indices, and so it may be considered a useful adjunct for detecting subtle proximal caries lesions (17). Given this, we used the sharpen filter to compare with emboss; the other studies are about other filter enhancements.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing popularity of digital radiography, only a few patients have benefitted from its perks because of the fact that many capabilities of these systems are ignored and not routinely used (15)(16)(17)(18). Some studies mentioned this ability and emphasized more on the agreement among observers (8-10); concurrently, some denied this objective and reported no difference in detecting subsurface proximal demineralization with various modalities (19,20). Haiter-Neto et al (2009) (11) reported no difference in detection potential between raw images of PSP and those processed with task-specific filters, but they recommended the application of fine enhancement for initial slight caries detection even if there is no considerable effect on diagnostic accuracy.…”
mentioning
confidence: 99%
“…However, this supposition requires more investigation. Belem et al (2013) (20) evaluated the impaction of enhanced digital radiography in proximal caries detection and reported increased sensitivity and accuracy with sharpening; however, they found that negative filtering led to a decrease in accuracy. Mehr-Alizadeh et al (2012) (22) also reported increased sensitivity, positive predictive value, negative predictive value, and diagnostic accuracy of the zoomed images rather than the basics in their study on the diagnostic accuracy of dentinal occlusal caries detection.…”
mentioning
confidence: 99%